Amercian Poets & Poetry - Rich, Adrienne & Wilbur, Richard (Lahore New Kitab Mahal)
Adrienne Rich is a American Poets of this age.she was born in Baltimore ,Maryland on May 16,1929.Her father Anrold Rich appreciated her literary,talent and encouraged her to write.
Include : Bibliography
Keywords: Amercian Poets & Poetry -- English Litrature -- Fusion of poetry and politics -- Richard Wilbur 's World